More than just temperature: the effects of nest relocation on incubation environment and hatchling quality in green turtles (Chelonia mydas) - David Dor; David T. Booth; Lisa E. Schwanz (Marine Biology, 2026)
Nest relocation and shading are widely used conservation strategies intended to mitigate threats to marine turtle hatchling survival. However, these interventions may carry unintended fitness costs. Estimating such effects can be challenging, especially in the absence of opportunities to compare with natural, undisturbed nests. Green turtle ( Chelonia mydas ) clutches were assigned to one of three treatments ( in situ , shaded relocation, or unshaded relocation) on Heron Island, Queensland, Australia (23.44307° S, 151.91809° E), during two nesting seasons (Dec 2022 – Feb 2023 and Dec 2023 – Feb 2024). Incubation temperature, hatching and emergence success, sex ratio, morphology (carapace size and body mass), and performance (self-righting ability and crawl speed) were assessed. Relocated unshaded nests exhibited higher incubation temperatures than in situ and shaded nests, especially during the final two weeks of incubation. Consequently, warmer nests produced smaller hatchlings with higher mass relative to size (residual mass) and poorer self-righting performance. Notably, in situ and shaded relocated nests had comparable incubation temperatures, yet still differed in hatching success, hatchling size, and self-righting ability, indicating that relocation can carry developmental consequences independent of those related to thermal averages. These findings highlight the importance of prioritising in situ nesting where feasible and accounting for both thermal and non-thermal factors of relocation sites if relocation is required.

Roadless rule rescission threatens highest integrity forest ecosystems in the United States - David J. Mildrexler; Logan T. Berner; Beverly E. Law; Mary S. Booth (Biological Conservation, 2026)

Co-production of low technical readiness level climate science through prototyping with users. Prospects in a European case study - E. Delpiazzo; K. Bülow; E. Baulenas Serra; C. Teichmann; J.H. Christensen; D. Matte; D. Bojovic; P. Kalverla; B.B. B. Booth; C.R. Goddard; F. Fung; B. Solaraju-Murali; et al. (Environmental Science & Policy, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Navigating Narratives: An Exploratory Scoping Review on the Framing of the Illegal, Unreported and Unregulated Fishing Research - Brittany Bartlett; Rodrigo Oyanedel; Hollie Booth; Stefanía Ásta Karlsdóttir; Amaël Dupaix; Ariel Greiner; M. Isidora Ávila‐Thieme; Juan Andrés Silva; Shathuki Perera; Mayuri Chopra; E. J. Milner‐Gulland (Fish and Fisheries, 2026)
Sustainable fisheries are often undermined by illegal, unreported and, in some cases, unregulated fishing (collectively, IUU fishing). As such, it is critical to ensure that current research effectively informs practical fisheries management interventions. We conducted an exploratory scoping review of 509 scholarly articles to assess general trends related to how IUU fishing is framed and distributed in the literature, identifying prevailing narratives that may influence governance. Research on the topic of IUU fishing has increased over time, although geographic distributions in terms of study locations and lead authorship do not necessarily align with global hotspots and priorities. While most location‐specific studies include at least one author affiliated with an institution from the region being studied, a bias remains towards first authors from high‐income countries. Moreover, while there is a justified focus on the Western Pacific Ocean, other vulnerable regions, such as the West Indian Ocean, remain comparatively underrepresented. Contrary to the assumption of a social science deficit in marine conservation, over half of the articles categorised applied a primarily social science lens; however, coverage from the behavioural sciences was limited. A subset analysis revealed a strong emphasis on large‐scale illegal fishing, with frequent conceptual blurring across fishery scales and IUU components. These patterns suggest a high‐level and often ambiguous framing of IUU fishing, which may risk oversimplifying complex issues and diluting context‐specific nuances. We recommend a shift towards more grounded and solutions‐oriented research, with more focus on unreported and unregulated fishing, particularly in small‐scale contexts and underrepresented locations.

In poor taste: leaf palatability traits are not correlated with aboveground enemy release - Zoe A. Xirocostas; Eve Slavich; Susan E. Everingham; Juha-Pekka Salminen; Louis Booth; Roslyn Gleadow; Jeff Ollerton; Riin Tamme; Begoña Peco; Vincent Lesieur; S. Raghu; Robert R. Junker; et al. (Oecologia, 2026)

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

Trade regulations drive improved global shark and ray management - Mark E. Bond; Hollie Booth; Akshay Tanna; Sarah L. Fowler; Carlos J. Polo-Silva; K.H. Stanley Shea; Floriane Cardiec; Elisabeth F. Mansur; Rima W. Jabado (Marine Policy, 2025)

Purification of uranium tetrafluoride using ammonium bifluoride - Kyle R. Foster; Juliano Schorne-Pinto; Ronald E. Booth; Annabelle Husek; Mina Aziziha; Hunter B. Tisdale; Bernie W.N. Fitzpatrick; Hans-Conrad zur Loye; Markus H.A. Piro; Theodore M. Besmann (Journal of Fluorine Chemistry, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Observations on the role of internal sand moisture dynamics in wave-driven dune face erosion - S. Conti; K.D. Splinter; E. Booth; D. Djadjiguna; I.L. Turner (Geomorphology, 2024)

The impact of gastrointestinal parasitism on the behaviour and welfare of weaned housed lambs - Michelle C. Reeves; Naomi Booth; Naomi J. Fox; Jo Donbavand; Mhairi Jack; Fiona Kenyon; Jessica E. Martin; Emma M. Baxter; Cathy M. Dwyer (Applied Animal Behaviour Science, 2024)

Further insights into killer whales Orcinus orca preying on white sharks Carcharodon carcharias in South Africa - A Towner; P Micarelli; D Hurwitz; MJ Smale; AJ Booth; C Stopforth; E Jacobs; FR Reinero; V Ricci; A Di Bari; S Gavazzi; G Carugno; et al. (African Journal of Marine Science, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Short‐term resilience to climate‐induced temperature increases for equatorial sea turtle populations - Melissa N. Staines; Hayley Versace; Jacques‐Olivier Laloë; Caitlin E. Smith; Christine A. Madden Hof; David T. Booth; Ian R. Tibbetts; Graeme C. Hays (Global Change Biology, 2023)
Projection models are being increasingly used to manage threatened taxa by estimating their responses to climate change. Sea turtles are particularly susceptible to climate change as they have temperature‐dependent sex determination and increased sand temperatures on nesting beaches could result in the ‘feminisation’ of hatchling sex ratios for some populations. This study modelled likely long‐term trends in sand temperatures and hatchling sex ratios at an equatorial nesting site for endangered green turtles ( Chelonia mydas ) and critically endangered hawksbill turtles ( Eretmochelys imbricata ). A total of 1078 days of sand temperature data were collected from 28 logger deployments at nest depth between 2018 and 2022 in Papua New Guinea (PNG). Long‐term trends in sand temperature were generated from a model using air temperature as an environmental proxy. The influence of rainfall and seasonal variation on sand temperature was also investigated. Between 1960 and 2019, we estimated that sand temperature increased by ~0.6°C and the average hatchling sex ratio was relatively balanced (46.2% female, SD = 10.7). No trends were observed in historical rainfall anomalies and projections indicated no further changes to rainfall until 2100. Therefore, the sex ratio models were unlikely to be influenced by changing rainfall patterns. A relatively balanced sex ratio such as this is starkly different to the extremely female‐skewed hatchling sex ratio (>99% female) reported for another Coral Sea nesting site, Raine Island (~850 km West). This PNG nesting site is likely rare in the global context, as it is less threatened by climate‐induced feminisation. Although there is no current need for ‘cooling’ interventions, the mean projected sex ratios for 2020–2100 were estimated 76%–87% female, so future interventions may be required to increase male production. Our use of long‐term sand temperature and rainfall trends has advanced our understanding of climate change impacts on sea turtles.

Exploring contaminants as a disruptor of temperature-dependent sex determination in sea turtle hatchlings - Arthur D. Barraza; Larissa Young; Caitlin E. Smith; David T. Booth; Christine A. Madden Hof; Kimberly A. Finlayson; Frederic D. L. Leusch; Jason P. van de Merwe (Frontiers in Marine Science, 2023)
Sea turtle nesting beaches are experiencing increased sand temperatures as climate change progresses. In one major green turtle ( Chelonia mydas ) nesting beach in the northern Great Barrier Reef, over 99 percent of hatchlings are female. The effects of contaminants on sea turtle hatchling sex determination are not often explored. Liver samples were collected from green turtle hatchlings that were sacrificed for histological sex determination in a parallel study on the effects of sand cooling on sex ratios, and analysed for trace elements via acid digestion and organic contaminants via in vitro cytotoxicity bioassays. Chromium, antimony, barium, and cadmium have previously been demonstrated to be estrogenic, and concentrations of these elements were used to calculate three estrogenic indexes for each clutch: predicted relative estrogenic potency (PEEQA), the sum of percent trace elements above the median of all samples (TEOM), and the sum of percent estrogenic elements above the median of all samples (EstroEOM). Excluding an outlier clutch, cadmium, antimony, and EstroEOM had significant positive relationships with sex ratio deviation. Mean clutch cobalt, lead, antimony and barium, also had a significant positive relationship with clutch sex ratio. There was no relationship between in vitro cytotoxicity of liver extracts and sex ratio, however, 9% of hatchlings had organic contaminants high enough to suggest potential cellular damage. Contaminant effects on sex determination are likely to be caused by a mixture of contaminant interactions as well as temperature. Many trace elements detected in this study have also been linked to negative health effects on hatchlings in previous studies. Considering the risks of feminization due to climate change and potential contaminant effects on hatchling health and sex determination, future studies exploring contaminant effects on sea turtle hatchling sex determination are recommended.

The utility of otolith-based methods for discriminating stock structure of the fishery important monacanthid, Nelusetta ayraud, over an intermediate scale - Holly Gunton; Ashley M. Fowler; Marcus E. Miller; David J. Booth; John Stewart (Fisheries Research, 2023)

Heritage genetics for adaptation to marginal soils in barley - Sidsel Birkelund Schmidt; Lawrie K. Brown; Allan Booth; John Wishart; Pete E. Hedley; Peter Martin; Søren Husted; Timothy S. George; Joanne Russell (Trends in Plant Science, 2023)

Operational sex ratio estimated from drone surveys for a species threatened by climate warming - Melissa N. Staines; Caitlin E. Smith; Christine A. Madden Hof; David T. Booth; Ian R. Tibbetts; Graeme C. Hays (Marine Biology, 2022)
Rising sand temperatures resulting from climate warming may cause the ‘feminization’ of sea turtle populations, which have temperature-dependent sex determination. In July and October 2021, we conducted surveys using a drone (also referred to as an unmanned aerial vehicle or UAV) and shore-based observations to assess the operational sex ratio (OSR) (number of males and females in breeding condition) for green turtles ( Chelonia mydas ) in the southern Great Barrier Reef, Australia (23.44 °S, 151.92 °E). Using drone-imagery, the length:width (L:W) ratio of a turtle’s head was used to distinguish loggerhead turtles ( Caretta caretta ) from green turtles, and the L:W of the carapace was used to distinguish juveniles from adult-sized green turtles. The first breeding pair was observed in shore-based surveys on 14 September 2021 and the number of mating turtles then increased to a peak on 4 October, about 8 weeks before the peak in nesting. A total of 94 km of drone transects with associated video footage was analysed. In October, at the peak of the mating season, the ratio of adult turtles displaying breeding behaviours near the island was 0.51 female (95% CI ± 0.17), supporting previous conclusions that despite the female-biased (> 80%) hatchling sex ratio, this population likely has a fairly balanced OSR. These findings are likely explained by males breeding 2–3 times more frequently than females, which helps mitigate female-biased hatchling sex ratios. Assessing the OSR of populations with extreme female hatchling bias may help to inform whether intervention is needed to increase male hatchling production.

Criteria for Preliminary Risk Assessment of Brownfield Site: An International Survey of Experts - Charf Mahammedi; Lamine Mahdjoubi; Colin Booth; Russell Bowman; Talib E. Butt (Environmental Management, 2022)
Comprehensive risk assessment of brownfield sites requires a broad range of knowledge and multi-disciplinary expertise. Whilst the identification of criteria requirements for preliminary risk assessment has received some attention, there appears to be no studies that have specifically examined professional perspectives relating to these requirements. Yet, variations in professional practitioners’ assessments may have significant consequences for the assessment of risks, and how the criteria are imparted to stakeholders. This study aims to identify the criteria requirements for preliminary risk assessment, using the pollutant linkage model (Source–Pathway–Receptor), and explores cross-disciplinary professional perspectives related to these requirements. To this end, this study commenced with a systematic review to identify various criteria streams required for the preliminary risk assessment of brownfield sites. Thereafter, a questionnaire survey was design and shared with brownfield site professionals. Quantitative analysis of the survey responses ( n = 76) reveals disciplines have markedly different priorities relating to the same hazard. For instance, geophysicists, geochemists, and hydrologists do not raise concerns regarding ground movement that can result from the removal of storage and tanks, whilst the same hazard was considered as having a high importance by other professions (such as geologists and geotechnical engineers). This example, amongst others revealed in the study, underpins potential issues and implications for various stakeholders compiling and/or using preliminary risk assessment criteria. This study clarifies both the key criteria requirements for the preliminary risk assessment of brownfield sites, as well as the importance of recognising how variation in professionals’ perceptions plays in the risk assessment process. Although, specialist knowledge is essential for brownfield site investigation, so is the maintaining a broad-based view of other experts coming from different backgrounds, as this renders holistic risk assessment insights.

Grazing Increases Soil Warming in Headwater Wetlands: Importance to Land Managers and Water Users - D. Terrance Booth; John C. Likins; Samuel E. Cox; Jay B. Norton; Richard C. Anderson-Sprecher (Ecosystems, 2022)
The earth’s mountains continue to lose water. Glaciers are melting and mountain snow/rain balance tilts increasingly liquescent. Water is running off sooner—sometimes overfilling reservoirs, causing flooding, and setting the stage for late-season shortages. One adaptive strategy is to recover and enhance water-storage capacities of headwater riparian systems. Grazing, a common use of headwater lands, affects both soils and vegetation. To better understand how grazing might affect water storage and other ecosystem services of high elevation riparian wetlands, we measured soil-profile temperatures, soil organic matter (SOM), and phytomass at six sites in the upper Sweetwater River sub-basin of Wyoming, USA, where fence lines allowed us to contrast grazing management. We found grazed wetlands consistently had warmer soils than fenced wetlands. We found added evidence that SOM is important in both soil temperature control and water-storage potential of wetlands. We review evidence that warmer soil temperatures and drying cause loss of SOM with the implied concomitant C losses through erosion and emissions. We recommend land managers of temperate-climate headwater systems consider the need to end growing seasons with full stands of riparian vegetation to reduce soil warming and to build organic matter—particularly on lands where municipalities and other downstream water users are seeking long-term increases in water yields and less flooding.

Modeling population effects of the Deepwater Horizon oil spill on a long‐lived species - Lori H. Schwacke; Tiago A. Marques; Len Thomas; Cormac G. Booth; Brian C. Balmer; Ashley Barratclough; Kathleen Colegrove; Sylvain De Guise; Lance P. Garrison; Forrest M. Gomez; Jeanine S. Morey; Keith D. Mullin; et al. (Conservation Biology, 2022)
The 2010 Deepwater Horizon (DWH) oil spill exposed common bottlenose dolphins ( Tursiops truncatus ) in Barataria Bay, Louisiana to heavy oiling that caused increased mortality and chronic disease and impaired reproduction in surviving dolphins. We conducted photographic surveys and veterinary assessments in the decade following the spill. We assigned a prognostic score (good, fair, guarded, poor, or grave) for each dolphin to provide a single integrated indicator of overall health, and we examined temporal trends in prognostic scores. We used expert elicitation to quantify the implications of trends for the proportion of the dolphins that would recover within their lifetime. We integrated expert elicitation, along with other new information, in a population dynamics model to predict the effects of observed health trends on demography. We compared the resulting population trajectory with that predicted under baseline (no spill) conditions. Disease conditions persisted and have recently worsened in dolphins that were presumably exposed to DWH oil: 78% of those assessed in 2018 had a guarded, poor, or grave prognosis. Dolphins born after the spill were in better health. We estimated that the population declined by 45% (95% CI 14–74) relative to baseline and will take 35 years (95% CI 18–67) to recover to 95% of baseline numbers. The sum of annual differences between baseline and injured population sizes (i.e., the lost cetacean years) was 30,993 (95% CI 6607–94,148). The population is currently at a minimum point in its recovery trajectory and is vulnerable to emerging threats, including planned ecosystem restoration efforts that are likely to be detrimental to the dolphins’ survival. Our modeling framework demonstrates an approach for integrating different sources and types of data, highlights the utility of expert elicitation for indeterminable input parameters, and emphasizes the importance of considering and monitoring long‐term health of long‐lived species subject to environmental disasters. Article impact statement : Oil spills can have long‐term consequences for the health of long‐lived species; thus, effective restoration and monitoring are needed.

A decision support tool for integrated fisheries bycatch management - Eric Gilman; Martin Hall; Hollie Booth; Trisha Gupta; Milani Chaloupka; Hannah Fennell; Michel J. Kaiser; Divya Karnad; E. J. Milner-Gulland (Reviews in Fish Biology and Fisheries, 2022)
Participatory decision tools enable stakeholders to reconcile conflicting natural resources management objectives. Fisheries targeting highly productive species can have profound impacts on co-occurring bycatch species with low fecundity and other life history traits that make them vulnerable to anthropogenic sources of mortality. This study developed a decision tool for integrated bycatch management for data-limited to data-rich fisheries, improving upon current piecemeal approaches. First, through a systematic literature review, participants compile a comprehensive database of methods to mitigate the catch and fishing mortality of threatened bycatch species. These mitigation methods are then categorized into tiers of a sequential mitigation hierarchy, where interventions that avoid capture are considered before those that minimize catchability, followed by methods that minimize fishing mortality, before approaches that offset residual impacts. The methods are also assembled within an evidence hierarchy, where findings from meta-analytic modelling studies are more robust and generalizable than from individual studies. The decision tool enables stakeholders to evaluate alternative bycatch management strategies’ efficacy at meeting specific and measurable objectives for mitigating the catch and mortality of bycatch and for costs from multispecies conflicts, economic viability, practicality and safety, while accounting for the fishery-specific feasibility of compliance monitoring of alternative bycatch management measures. Ongoing adaptation of the bycatch management framework addresses findings from performance assessments, updated evidence, new mitigation methods and changes to governance systems. The proposed decision tool therefore enables stakeholders to develop bycatch management frameworks that provide precautionary protection for the most vulnerable populations with acceptable tradeoffs.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fear at the top: killer whale predation drives white shark absence at South Africa’s largest aggregation site - AV Towner; RGA Watson; AA Kock; Y Papastamatiou; M Sturup; E Gennari; K Baker; T Booth; M Dicken; W Chivell; S Elwen; T Kaschke; et al. (African Journal of Marine Science, 2022)

A pathogenic deletion in Forkhead Box L1 (FOXL1) identifies the first otosclerosis (OTSC) gene - Nelly Abdelfatah; Ahmed A. Mostafa; Curtis R. French; Lance P. Doucette; Cindy Penney; Matthew B. Lucas; Anne Griffin; Valerie Booth; Christopher Rowley; Jessica E. Besaw; Lisbeth Tranebjærg; Nanna Dahl Rendtorff; et al. (Human Genetics, 2022)
Otosclerosis is a bone disorder of the otic capsule and common form of late-onset hearing impairment. Considered a complex disease, little is known about its pathogenesis. Over the past 20 years, ten autosomal dominant loci ( OTSC1-10 ) have been mapped but no genes identified. Herein, we map a new OTSC locus to a 9.96 Mb region within the FOX gene cluster on 16q24.1 and identify a 15 bp coding deletion in Forkhead Box L1 co-segregating with otosclerosis in a Caucasian family. Pre-operative phenotype ranges from moderate to severe hearing loss to profound sensorineural loss requiring a cochlear implant. Mutant FOXL1 is both transcribed and translated and correctly locates to the cell nucleus. However, the deletion of 5 residues in the C-terminus of mutant FOXL1 causes a complete loss of transcriptional activity due to loss of secondary (alpha helix) structure. FOXL1 (rs764026385) was identified in a second unrelated case on a shared background. We conclude that FOXL1 (rs764026385) is pathogenic and causes autosomal dominant otosclerosis and propose a key inhibitory role for wildtype Foxl1 in bone remodelling in the otic capsule. New insights into the molecular pathology of otosclerosis from this study provide molecular targets for non-invasive therapeutic interventions.

Correction to: Treatment decision‑making in sickle cell disease patients - A. Booth; V. Bonham; M. Porteus; K. E. Ormond (Journal of Community Genetics, 2022)

Treatment decision-making in sickle cell disease patients - A. Booth; V. Bonham; M. Porteus; K. E. Ormond (Journal of Community Genetics, 2022)

The impact of varicella vaccination on paediatric herpes zoster epidemiology: a Canadian population-based retrospective cohort study - Ellen Rafferty; Laura Reifferscheid; Margaret L. Russell; Stephanie Booth; Lawrence W. Svenson; Shannon E. MacDonald (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The impact of universal varicella vaccination on herpes zoster (HZ) risk in unvaccinated and vaccinated children, and its long-term influence on HZ epidemiology, remains unknown. We conducted a retrospective cohort study using population-based administrative health data for children born between 1993 and 2018 (n = 924,124). We calculated age-specific cumulative HZ incidence rates by vaccination status for cohorts born before (1993–1999) and after (2000–2018) programme implementation; results were used to calculate relative risk of HZ by age group, vaccination status and vaccine availability period. Annual HZ incidence rates were calculated for 1993–2018. HZ risk was higher among unvaccinated children compared to vaccinated children across age groups; 64% higher before universal vaccination (RR: 0.36, 95% CI: 0.33, 0.39), and 32% higher after universal vaccination (RR: 0.68, 95% CI: 0.64, 0.73). Among unvaccinated children, HZ risk was 60% lower after vaccine programme implementation (RR: 0.40, 95% CI: 0.38, 0.43). Two-dose receipt corresponded with a 41% lower risk of HZ compared to one-dose receipt (RR: 0.59, 95% CI: 0.53, 0.65). Crude annual HZ incidence rates declined 64% after programme implementation, with decreases observed across age groups. Universal varicella vaccination programme implementation corresponds to decreased paediatric HZ incidence across age groups, in both vaccinated and unvaccinated individuals. Results from this study can be used to help inform varicella vaccination programme decision-making in other countries.

GliMR: Cross-Border Collaborations to Promote Advanced MRI Biomarkers for Glioma - Patricia Clement; Thomas Booth; Fran Borovečki; Kyrre E. Emblem; Patrícia Figueiredo; Lydiane Hirschler; Radim Jančálek; Vera C. Keil; Camille Maumet; Yelda Özsunar; Cyril Pernet; Jan Petr; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose There is an annual incidence of 50,000 glioma cases in Europe. The optimal treatment strategy is highly personalised, depending on tumour type, grade, spatial localization, and the degree of tissue infiltration. In research settings, advanced magnetic resonance imaging (MRI) has shown great promise as a tool to inform personalised treatment decisions. However, the use of advanced MRI in clinical practice remains scarce due to the downstream effects of siloed glioma imaging research with limited representation of MRI specialists in established consortia; and the associated lack of available tools and expertise in clinical settings. These shortcomings delay the translation of scientific breakthroughs into novel treatment strategy. As a response we have developed the network “Glioma MR Imaging 2.0” (GliMR) which we present in this article. Methods GliMR aims to build a pan-European and multidisciplinary network of experts and accelerate the use of advanced MRI in glioma beyond the current “state-of-the-art” in glioma imaging. The Action Glioma MR Imaging 2.0 (GliMR) was granted funding by the European Cooperation in Science and Technology (COST) in June 2019. Results GliMR’s first grant period ran from September 2019 to April 2020, during which several meetings were held and projects were initiated, such as reviewing the current knowledge on advanced MRI; developing a General Data Protection Regulation (GDPR) compliant consent form; and setting up the website. Conclusion The Action overcomes the pre-existing limitations of glioma research and is funded until September 2023. New members will be accepted during its entire duration.

Predicting Geographic Ranges of Marine Animal Populations Using Stable Isotopes: A Case Study of Great Hammerhead Sharks in Eastern Australia - Vincent Raoult; Clive N. Trueman; Kelsey M. Kingsbury; Bronwyn M. Gillanders; Matt K. Broadhurst; Jane E. Williamson; Ivan Nagelkerken; David J. Booth; Victor Peddemors; Lydie I. E. Couturier; Troy F. Gaston (Frontiers in Marine Science, 2020)
Determining the geographic range of widely dispersed or migratory marine organisms is notoriously difficult, often requiring considerable costs and typically extensive tagging or exploration programs. While these approaches are accurate and can reveal important information on the species, they are usually conducted on only a small number of individuals and can take years to produce relevant results, so alternative approaches may be preferable. The presence of latitudinal gradients in stable carbon isotope compositions of marine phytoplankton offers a means to quickly determine likely geographic population ranges of species that rely on productivity from these resources. Across sufficiently large spatial and temporal scales, the stable carbon isotopes of large coastal or pelagic marine species should reflect broad geographic patterns of resource use, and could be used to infer geographic ranges of marine populations. Using two methods, one based on a global mechanistic model and the other on targeted low-cost latitudinal sampling of fishes, we demonstrate and compare these stable isotope approaches to determine the core population geography of an apex predator, the great hammerhead ( Sphyrna mokarran ). Both methods indicated similar geographic ranges and suggested that S. mokarran recorded in south-eastern Australia are likely to be from more northern Australian waters. These approaches could be replicated in other areas where coastlines span predictable geographic gradients in isotope values and be used to determine the core population geography of highly mobile species to inform management decisions.

Association mapping of malting quality traits in UK spring and winter barley cultivar collections - Mark E. Looseley; Luke Ramsay; Hazel Bull; J. Stuart Swanston; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Joanne R. Russell; Robbie Waugh; William T. B. Thomas (Theoretical and Applied Genetics, 2020)
Key message Historical malting quality data was collated from UK national and recommended list trial data and used in a GWAS. 25 QTL were identified, with the majority from spring barley cultivar sets. Abstract In Europe, the most economically significant use of barley is the production of malt for use in the brewing and distilling industries. As such, selection for traits related to malting quality is of great commercial interest. In order to study the genetic basis of variation for malting quality traits in UK cultivars, a historical set of trial data was collated from national and recommended list trials from the period 1988 to 2016. This data was used to estimate variety means for 20 quality related traits in 451 spring barley cultivars, and 407 winter cultivars. Genotypes for these cultivars were generated using iSelect 9k and 50k genotyping platforms, and a genome wide association scan performed to identify malting quality quantitative trait loci (QTL). 24 QTL were identified in spring barley cultivars, and 2 from the winter set. A number of these correspond to known malting quality related genes but the remainder represents novel genetic variation that is accessible to breeders for the genetic improvement of new cultivars.

Mitigation of Elasmobranch Bycatch in Trawlers: A Case Study in Indian Fisheries - Trisha Gupta; Hollie Booth; William Arlidge; Chetan Rao; Muralidharan Manoharakrishnan; Naveen Namboothri; Kartik Shanker; E. J. Milner-Gulland (Frontiers in Marine Science, 2020)

A Mitigation Hierarchy Approach for Managing Sea Turtle Captures in Small-Scale Fisheries - William N. S. Arlidge; Dale Squires; Joanna Alfaro-Shigueto; Hollie Booth; Jeffrey C. Mangel; E. J. Milner-Gulland (Frontiers in Marine Science, 2020)

Correction to: Overexpression of Protein Kinase Inhibitor Alpha Reverses Rat Low Voluntary Running Behavior - Kolter B. Grigsby; Gregory N. Ruegsegger; Thomas E. Childs; Frank W. Booth (Molecular Neurobiology, 2019)

Overexpression of Protein Kinase Inhibitor Alpha Reverses Rat Low Voluntary Running Behavior - Kolter B. Grigsby; Gregory N. Ruegsegger; Thomas E. Childs; Frank W. Booth (Molecular Neurobiology, 2019)

Resistance to Rhynchosporium commune in a collection of European spring barley germplasm - Mark E. Looseley; Lucie L. Griffe; Bianca Büttner; Kathryn M. Wright; Jill Middlefell-Williams; Hazel Bull; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Günther Schweizer; Joanne R. Russell; Robbie Waugh; et al. (Theoretical and Applied Genetics, 2018)

Do differences in future sulfate emission pathways matter for near-term climate? A case study for the Asian monsoon - Rachel E. Bartlett; Massimo A. Bollasina; Ben B. B. Booth; Nick J. Dunstone; Franco Marenco; Gabriele Messori; Dan J. Bernie (Climate Dynamics, 2018)

Comparative stability of Major Facilitator Superfamily transport proteins - Nicola J. Harris; Heather E. Findlay; Michael R. Sanders; Mateusz Kedzierski; Ália dos Santos; Paula J. Booth (European Biophysics Journal, 2017)

Blubber cortisol qualitatively reflects circulating cortisol concentrations in bottlenose dolphins - Cory D. Champagne; Nicholas M. Kellar; Daniel E. Crocker; Samuel K. Wasser; Rebecca K. Booth; Marisa L. Trego; Dorian S. Houser (Marine Mammal Science, 2017)
Stress hormones, released into circulation as a consequence of disturbance, are classically assayed from blood samples but may also be detected in a variety of matrices. Blubber and fecal samples can be remotely collected from free‐ranging cetaceans without the confounding hormone elevations associated with chase, capture, and handling required to collect blood samples. The relationship between cortisol concentrations in circulation with that of blubber and feces, however, is unknown. To assess these associations, we elevated cortisol by orally administering hydrocortisone for five days in five bottlenose dolphins. Voluntary blood and fecal samples were collected daily; blubber biopsies were collected on day one, just prior to hydrocortisone administration, and days three and five of hydrocortisone administration. We evaluated subsequent changes in several circulating stress hormones as well as cortisol and glucocorticoid metabolites in blubber and feces, respectively. There was a significant association between cortisol levels in serum and in blubber ( F 1,12.7 = 14.3, P mR 2 = 0.57) despite substantial variability in blubber cortisol levels. Counterintuitively, fecal cortisol metabolite levels were inversely related to serum cortisol. The relationship between serum and blubber cortisol levels suggests blubber samples from remote sampling may be useful to detect stress loads in this species.

Workshop Report: Crystal City VI—Bioanalytical Method Validation for Biomarkers - Mark E. Arnold; Brian Booth; Lindsay King; Chad Ray (The AAPS Journal, 2016)

Microbial and Environmental Controls of Methane Fluxes Along a Soil Moisture Gradient in a Pacific Coastal Temperate Rainforest - Jesper Riis Christiansen; David Levy-Booth; Cindy E. Prescott; Sue J. Grayston (Ecosystems, 2016)

Comprehensive genetic testing in the clinical evaluation of 1119 patients with hearing loss - Christina M. Sloan-Heggen; Amanda O. Bierer; A. Eliot Shearer; Diana L. Kolbe; Carla J. Nishimura; Kathy L. Frees; Sean S. Ephraim; Seiji B. Shibata; Kevin T. Booth; Colleen A. Campbell; Paul T. Ranum; Amy E. Weaver; et al. (Human Genetics, 2016)

Headcut Erosion in Wyoming’s Sweetwater Subbasin - Samuel E. Cox; D. Terrance Booth; John C. Likins (Environmental Management, 2016)

Fenceline contrasts: grazing increases wetland surface roughness - D. T. Booth; S. E. Cox; J. C. Likins (Wetlands Ecology and Management, 2015)

Stable isotope relationships between mothers, eggs and hatchlings in loggerhead sea turtles Caretta caretta - Alice S. Carpentier; David T. Booth; Karen E. Arthur; Colin J. Limpus (Marine Biology, 2015)

Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Brian Booth; Mark E. Arnold; Binodh DeSilva; Lakshmi Amaravadi; Sherri Dudal; Eric Fluhler; Boris Gorovits; Sam H. Haidar; John Kadavil; Steve Lowes; Robert Nicholson; Marie Rock; et al. (The AAPS Journal, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

A generic method for climate change impact analysis of tree species planting domains - Trevor H. Booth; Tom Jovanovic; Chris E. Harwood (New Forests, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Growth and temperature relationships for juvenile fish species in seagrass beds: implications of climate change - D. J. Booth; D. E. Poulos; J. Poole; D. A. Feary (Journal of Fish Biology, 2014)
The effect of water temperature on growth responses of three common seagrass fish species that co‐occur as juveniles in the estuaries in Sydney (34° S) but have differing latitudinal ranges was measured: Pelates sexlineatus (subtropical to warm temperate: 27–35° S), Centropogon australis (primarily subtropical to warm temperate: 24–37° S) and Acanthaluteres spilomelanurus (warm to cool temperate: below 32° S). Replicate individuals of each species were acclimated over a 7 day period in one of three temperature treatments (control: 22° C, low: 18° C and high: 26° C) and their somatic growth was assessed within treatments over 10 days. Growth of all three species was affected by water temperature, with the highest growth of both northern species ( P. sexlineatus and C. australis ) at 22 and 26° C, whereas growth of the southern ranging species ( A. spilomelanurus ) was reduced at temperatures higher than 18° C, suggesting that predicted increase in estuarine water temperatures through climate change may change relative performance of seagrass fish assemblages.

Meeting Report: Metabolites in Safety Testing (MIST) Symposium—Safety Assessment of Human Metabolites: What’s REALLY Necessary to Ascertain Exposure Coverage in Safety Tests? - Hongying Gao; Abigail Jacobs; Ronald E. White; Brian P. Booth; R. Scott Obach (The AAPS Journal, 2013)

EEFIT mission to Haiti following the 12th January 2010 earthquake - S. P. G. Madabhushi; K. Saito; E. D. Booth (Bulletin of Earthquake Engineering, 2013)

Drought as a Trigger for Rapid State Shifts in Kettle Ecosystems: Implications for Ecosystem Responses to Climate Change - Alex W. Ireland; Robert K. Booth; Sara C. Hotchkiss; Jennifer E. Schmitz (Wetlands, 2012)

The response of marine picoplankton to ocean acidification - Lindsay K. Newbold; Anna E. Oliver; Tim Booth; Bela Tiwari; Todd DeSantis; Michael Maguire; Gary Andersen; Christopher J. van der Gast; Andrew S. Whiteley (Environmental Microbiology, 2012)
Summary Since industrialization global CO 2 emissions have increased, and as a consequence oceanic pH is predicted to drop by 0.3–0.4 units before the end of the century – a process coined ‘ocean acidification’. Consequently, there is significant interest in how pH changes will affect the ocean's biota and integral processes. We investigated marine picoplankton (0.2–2 µm diameter) community response to predicted end of century CO 2 concentrations, via a ‘high‐CO 2 ’ (∼ 750 ppm) large‐volume (11 000 l) contained seawater mesocosm approach. We found little evidence of changes occurring in bacterial abundance or community composition due to elevated CO 2 under both phytoplankton pre‐bloom/bloom and post‐bloom conditions. In contrast, significant differences were observed between treatments for a number of key picoeukaryote community members. These data suggested a key outcome of ocean acidification is a more rapid exploitation of elevated CO 2 levels by photosynthetic picoeukaryotes. Thus, our study indicates the need for a more thorough understanding of picoeukaryote‐mediated carbon flow within ocean acidification experiments, both in relation to picoplankton carbon sources, sinks and transfer to higher trophic levels.

Differences in transcriptional patterns of extracellular matrix, inflammatory, and myogenic regulatory genes in myofibroblasts, fibroblasts, and muscle precursor cells isolated from old male rat skeletal muscle using a novel cell isolation procedure - Kevin A. Zwetsloot; Anders Nedergaard; Leigh T. Gilpin; Thomas E. Childs; Frank W. Booth (Biogerontology, 2012)

Phylogeography and species biogeography of montane Great Basin stoneflies - ALICIA S. SCHULTHEIS; JACKIE Y. BOOTH; LISA R. PERLMUTTER; JASON E. BOND; ANDREW L. SHELDON (Molecular Ecology, 2012)
Sky islands are ideal systems for determining the effects of climatic oscillations on species distributions and genetic structure. Our study focused on montane stonefly populations in the Great Basin of western North America. We used niche‐based distribution modelling, phylogeography and traditional species‐based biogeography to test several hypotheses as follows: (i) genetic differentiation among Doroneuria baumanni populations will be independent of hydrologic connectivity (headwater model); (ii) Sky islands were colonized when habitat was more continuous and populations likely experienced multiple expansions and contractions; (iii) Colonization events were coincident with the late Pleistocene and Holocene; and (iv) Shared topography and climate history will result in concordant patterns of genetic differentiation in D. baumanni and occurrences of 32 stonefly species across the region. Overall, Φ ST ’s and coalescent‐based estimates of migration were consistent with the headwater model. Maximum likelihood and Bayesian gene trees identified three major nonoverlapping east‐west clades. Distribution modelling indicated more suitable habitat in the Great Basin during the Last Glacial Maximum than at present, but none during the last interglacial period. Demographic analyses showed evidence of population expansion in one of the three major east–west clades. Intra‐clade divergence times (60 000–183 000 ybp) were well within the late Pleistocene while among‐clade divergence times (499 000–719 000 ybp) were deeper. Genetic differentiation in D. baumanni and distributions of stonefly species were significantly concordant. These results imply that climatic oscillations have played major roles in shaping the genetic structure and distributions of Great Basin stoneflies, but that divergence among clades occurred much earlier than our late Pleistocence/early Holocene predictions.

Computer-aided identification of coelacanths, Latimeria chalumnae , using scale patterns - Rosanne E. Thornycroft; Anthony J. Booth (Marine Biology Research, 2012)

Validation of otolith daily increment formation for two temperate syngnathid fishes: the pipefishes Stigmatopora argus and Stigmatopora nigra - K. L. Parkinson; D. J. Booth; J. E. Lee (Journal of Fish Biology, 2012)
Otoliths were used for the first time to successfully validate the age of members of the family Syngnathidae: the spotted pipefish Stigmatopora argus and the wide‐bodied pipefish Stigmatopora nigra . Otolith increments were deposited daily in (1) known‐age juveniles ranging in age from 0 to 31 days and (2) adults that had been stained with alizarin complexone, and a hatch mark was found on all otoliths which represented day 0. Otolith increment validation will allow development of growth models for S. argus and S. nigra , essential to understanding and managing these exclusive seagrass species.

Population genetic structure and colony breeding system in dampwood termites (Zootermopsis angusticollis and Z. nevadensis nuttingi) - W. Booth; C. S. Brent; D. V. Calleri; R. B. Rosengaus; J. F. A. Traniello; E. L. Vargo (Insectes Sociaux, 2012)

Linaria dalmatica invades south-facing slopes and less grazed areas in grazing-tolerant mixed-grass prairie - Dana M. Blumenthal; Andrew P. Norton; Samuel E. Cox; Erik M. Hardy; Glen E. Liston; Lisa Kennaway; D. Terrance Booth; Justin D. Derner (Biological Invasions, 2012)

Multi‐decadal drought and amplified moisture variability drove rapid forest community change in a humid region - Robert K. Booth; Stephen T. Jackson; Valerie A. Sousa; Maura E. Sullivan; Thomas A. Minckley; Michael J. Clifford (Ecology, 2012)
Climate variability, particularly the frequency of extreme events, is likely to increase in the coming decades, with poorly understood consequences for terrestrial ecosystems. Hydroclimatic variations of the Medieval Climate Anomaly (MCA) provide a setting for studying ecological responses to recent climate variability at magnitudes and timescales comparable to expectations of coming centuries. We examined forest response to the MCA in the humid western Great Lakes region of North America, using proxy records of vegetation, fire, and hydroclimate. Multi‐decadal moisture variability during the MCA was associated with a widespread, episodic decline in Fagus grandifolia (beech) populations. Spatial patterns of drought and forest changes were coherent, with beech declining only in areas where proxy‐climate records indicate that severe MCA droughts occurred. The occurrence of widespread, drought‐induced ecological changes in the Great Lakes region indicates that ecosystems in humid regions are vulnerable to rapid changes in drought magnitude and frequency.

Prevention of K-Ras- and Pten-mediated intravaginal tumors by treatment with camptothecin-loaded PLGA nanoparticles - Jeremy S. Blum; Caroline E. Weller; Carmen J. Booth; Imran A. Babar; Xianping Liang; Frank J. Slack; W. Mark Saltzman (Drug Delivery and Translational Research, 2011)

Arctic fisheries catches in Russia, USA, and Canada: baselines for neglected ecosystems - D. Zeller; S. Booth; E. Pakhomov; W. Swartz; D. Pauly (Polar Biology, 2011)

Metabolic adaptations of oxidative muscle during spawning migration in the Atlantic salmon Salmo salar L. - E. Bombardier; R. K. Booth; H. J. Green; R. S. McKinley (Fish Physiology and Biochemistry, 2010)

Malaria severity and human nitric oxide synthase type 2 (NOS2) promoter haplotypes - Marc C. Levesque; Maurine R. Hobbs; Charles W. O’Loughlin; Jennifer A. Chancellor; Youwei Chen; Ariana N. Tkachuk; Jennifer Booth; Kistie B. Patch; Sallie Allgood; Ann R. Pole; Carolyn A. Fernandez; Esther D. Mwaikambo; et al. (Human Genetics, 2010)

Elevated temperatures and carbon dioxide concentrations: effects on selected microbial activities in temperate agricultural soils - S. French; D. Levy-Booth; A. Samarajeewa; K. E. Shannon; J. Smith; J. T. Trevors (World Journal of Microbiology and Biotechnology, 2009)

Shadow attenuation with high dynamic range images - Samuel E. Cox; D. Terrance Booth (Environmental Monitoring and Assessment, 2009)

Dual-camera, high-resolution aerial assessment of pipeline revegetation - D. Terrance Booth; Samuel E. Cox (Environmental Monitoring and Assessment, 2009)

Ground-Cover Measurements: Assessing Correlation Among Aerial and Ground-Based Methods - D. Terrance Booth; Samuel E. Cox; Tim Meikle; Hans R. Zuuring (Environmental Management, 2008)

Home range of an estuarine‐dependent fish species Pomadasys commersonnii in a South African estuary - A.‐R. CHILDS; A. J. BOOTH; P. D. COWLEY; W. M. POTTS; T. F. NÆSJE; E. B. THORSTAD; F. ØKLAND (Fisheries Management and Ecology, 2008)
The home range and area use of spotted grunter, Pomadasys commersonnii (Haemulidae) (Lacepède), were investigated in the Great Fish estuary, South Africa. Forty individuals (263–698 mm TL) were surgically implanted with acoustic‐coded transmitters and manually tracked during two periods in 2003. Tagged fish spent on average 68 and 77% of the time in the estuary and the remaining time at sea during the two periods, respectively. While in the estuary, there was large variation in home range size, home range length and the number of home range areas amongst individuals. Larger fish had larger home ranges and more core areas than smaller fish. The home ranges of 29 individuals (74%) occurred in the lower reaches of the estuary, suggesting that the proclamation of a no‐take zone in this high use area could benefit this over‐exploited estuarine fishery species.

Hydroelectricity and fish: a synopsis of comprehensive studies of upstream and downstream passage of anadromous wild Atlantic salmon, Salmo salar, on the Exploits River, Canada - D. A. Scruton; C. J. Pennell; C. E. Bourgeois; R. F. Goosney; L. King; R. K. Booth; W. Eddy; T. R. Porter; L. M. N. Ollerhead; K. D. Clarke (Hydrobiologia, 2008)

Measuring degradation of zinc phosphide residues in possum stomach contents - L. E. Brown; P. Fisher; G. Wright; L. Booth (Bulletin of Environmental Contamination and Toxicology, 2007)

Bio‐optical consequences of viral infection of phytoplankton: I. Experiments with the cyanobacterium, Synechococcus sp. - W. M. Balch; J. M. Vaughn; J. I. Goes; J. F. Novotny; D. T. Drapeau; E. S. Booth; C. L. Vining (Limnology and Oceanography, 2007)
Four strains of the cyanobacteria, Synechococcus , were infected with viruses isolated and purified from coastal waters of the Gulf of Maine. Changes in host and virus concentration were observed in time course experiments, along with associated variability in inherent optical properties. There were strong optical shifts before and after lysis in inherent optical properties on time scales commensurate with the viral infection process. Specifically, both backscattering and absorption (particularly in visible wavelengths) increased slightly after infection, but decreased markedly after lysis. The most rapid optical change was seen in in vivo chlorophyll fluorescence, with a slight increase within 2 d after initial infection. Such changes likely reflect fundamental changes in host photophysiology after infection. After host lysis, there was a major drop in bulk Chl a fluorescence, synchronous with a major increase in the ratio of free viruses per host cell. The net effect of the changes in fluorescence and host concentration was an increase in the fluorescence per cell. These optical changes were accompanied by major changes in the submicron particle size spectra as cells were lysed, releasing their intracellular contents.

Point Sampling Digital Imagery with ‘Samplepoint’ - D. Terrance Booth; Samuel E. Cox; Robert D. Berryman (Environmental Monitoring and Assessment, 2006)

A reanalysis of the relationship between strong westerlies and precipitation in the Great Plains and Midwest regions of North America - Robert K. Booth; John E. Kutzbach; Sara C. Hotchkiss; Reid A. Bryson (Climatic Change, 2006)

Precision Measurements from Very-Large Scale Aerial Digital Imagery - D. Terrance Booth; Samuel E. Cox; Robert D. Berryman (Environmental Monitoring and Assessment, 2006)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Effects of enhanced nitrogen deposition and phosphorus limitation on nitrogen budgets of semi‐natural grasslands - Gareth K. Phoenix; Rosemary E. Booth; Jonathan R. Leake; David J. Read; J. Philip Grime; John A. Lee (Global Change Biology, 2003)
Increased reactive atmospheric N deposition has been implicated in floristic changes in species‐rich acidic and calcareous grasslands, but the fate of this pollutant N in these ecosystems is unknown. This paper reports the first analysis of N budgets and N fluxes for two grasslands in the White Peak area of Derbyshire, one of the most heavily N‐polluted locations in the UK. N fluxes were monitored in lysimeter cores (retaining the original turfs) taken from field plots of unimproved acidic and calcareous grasslands that had received (in addition to ambient N deposition) simulated enhanced N deposition treatments of 3.5 and 14 g N m −2 yr −1 for 6 years. The influence of reducing phosphorus limitation was assessed by factorial additions of P. Seasonal leached losses of nitrate, ammonia and organic N were monitored in detail along with estimates of N removal through simulated grazing and gaseous losses through denitrification and volatilization. The rates of N fluxes by these pathways were used to create N budgets for the grasslands. Both grasslands were found to be accumulating much of the simulated additional N deposition: up to 89% accumulated in the calcareous grassland and up to 38% accumulated in the acidic grassland. The major fluxes of N loss from these grasslands were by simulated grazing and leaching of soluble organic N (constituting 90% of leached N under ambient conditions). Leached inorganic N (mainly nitrate) contributed significantly to the output flux of N under the highest N treatment only. Loss of N through ammonia volatilization accounted for less than 6% of the N added as simulated deposition, while denitrification contributed significantly to output fluxes only in the acidic grassland during winter. The implications of the results for ecosystem N balances and the likely consequences of N accumulation on these grasslands are discussed.

Wavelength-Resolved 3-Dimensional Fluorescence Lifetime Imaging - S. E. D. Webb; S. Lévêque-Fort; D. S. Elson; J. Siegel; T. Watson; M. J. Lever; M. Booth; R. Juskaitis; M. A. A. Neil; L. O. Sucharov; T. Wilson; P. M. W. French (Journal of Fluorescence, 2002)

Using PERT methodology in nuclear material safeguards and chemical process control - David E. Booth; Thomas L. Isenhour (Environmental Modeling & Assessment, 2000)

Nicotine self-administration in rats on a progressive ratio schedule of reinforcement - E. C. Donny; A. R. Caggiula; M. M. Mielke; S. Booth; M. A. Gharib; A. Hoffman; V. Maldovan; C. Shupenko; S. E. McCallum (Psychopharmacology, 1999)

Introgression of quantitative trait loci (QTLs) determining stripe rust resistance in barley: an example of marker-assisted line development - T. Toojinda; E. Baird; A. Booth; L. Broers; P. Hayes; W. Powell; W. Thomas; H. Vivar; G. Young (Theoretical and Applied Genetics, 1998)

Radio‐transmitted electromyogram signals as indicators of physical activity in Atlantic salmon - F. ØKland; B. Finstad; R. S. McKinley; E. B. Thorstad; R. K. Booth (Journal of Fish Biology, 1997)
Surgical methods developed to implant EMG (electromyogram) transmitters in Atlantic salmon Salmo salar were tested to calibrate electromyograms from axial red musculature to swimming speed in a swim speed chamber, and to compare electromyograms of fish from two stocks (Lone and Imsa). Ten Lone and eight Imsa salmon were equipped with internal EMG transmitters. Surgical procedures were acceptable, with 100% survival of all implanted fish during the study. It was possible to calibrate EMG pulse intervals to swimming speed in 14 of the 18 salmon run in the swim speed chamber ( r 2 = 0·35‐0·76 for individuals, 0·63 for pooled data). Individuals differed in their EMG resting levels (EMGs recorded at 0·5 ms −1 ), and so higher correlations were obtained between swimming speed and an activity index (EMG pulse intervals at different speeds/EMG resting levels) (pooled data, r 2 =0·75). The linear relationship between swimming speed and EMG pulse intervals differed significantly between the two stocks ( P

Molecular and biological characterization of new strains of murine cytomegalovirus isolated from wild mice - T. W. M. Booth; A. A. Scalzo; C. Carrello; P. A. Lyons; Helen E. Farrell; G. R. Singleton; G. R. Shellam (Archives of Virology, 1993)

Myzus persicae (Sulzer) in diffuse light and dark rustic storages and resultant PLRV transmission - Bruce L. Parker; Robert H. Booth; James E. Bryan (American Journal of Potato Research, 1983)

Syncytium formation caused by human cytomegalovirus in human embryonic lung fibroblasts - J. C. Booth; J. E. Beesley; H. Stern (Archives of Virology, 1978)

Preparation of rubella virus antigens for immunodiffusion by mild extraction of infected cells with a neutral detergent - J. Booth; E. Norrby (Archives of Virology, 1973)